Endocrine issues and premenopausal breast cancer - Mara Carsote; Diana Elena Rentea; Aida Petca; Stefania Zugravu; Claudia Mehedintu; Florica Sandru; Anda Dumitrascu; Mihai Cristian Dumitrascu (Romanian Journal of Medical Practice, 2021)
There is an alarming increasing incidence of PBC (premenopausal breast cancer) in countries with high income due to, on one hand, more accessible screening tools and, on the other hand, potential implications of daily lifestyle habits and endocrine disruptors of modern society on terms of facilitating tumor growth. A more severe prognostic is found in females younger than 40 years old at first detection, with advanced disease at diagnostic, and those with tumors displaying specific immunohistochemistry configuration (and associated gene profile) like ER (estrogen receptor) positive or HEGFR2 (human epidermal growth factor receptor) negative. Recently, particular aspects are reported in terms of PBC therapy: the switch from offering aromatase inhibitors/tamoxifen only in post-menopausal females was done to premenopausal subjects in addition to medication that offers ovarian function suppression (OFS) – as an alternative to classical oophorectomy - for 5 years up to 10 years extension depending on protocol and patient’ age at first diagnostic. The main endocrine considerations concerning PBC are: OFS and/or chemotherapy or oophorectomy causing prompt hypogonadism, bone status anomalies due to estrogens deficiency, potential endocrine tumors that are prone to be linked (for instance, a higher risk of cancer in acromegalic patients etc.), cardio-metabolic elements as facilitators of early tumorigenesis, fertility issues on PBC survivals etc. The purpose of the present paper is to introduce several key messages that relate to endocrine implications of PBC starting from a case.